The ESG Disclosure in Mitigating Information Asymmetry Risk: The Role of Corporate Governance - Norisnita, Muazila; Groda, Selvi Permata; Dwiridotjahjono, Jojok; Rihidima, Lidya Veronica Christy (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This research employs a Systematic Literature Review (SLR) to examine the relationship between Environmental, Social, and Governance (ESG) disclosure and the information asymmetry through corporate governance mechanisms in today’s dynamic business environment. Despite the growing adoption of ESG reporting to meet stakeholder demands, information asymmetry continues to impede efficient capital allocation and investor confidence. However, limited understanding remains on how corporate governance mechanisms shape ESG disclosure quality and its role in reducing information asymmetry. Several theories, including signaling, stakeholder, legitimacy, and agency theory, explain firms’ motivations for ESG reporting. While ESG disclosure is expected to reduce information asymmetry, its impact remains debated due to issues such as greenwashing, report credibility, and divergent investor perceptions. Prior studies reveal a generally negative association between ESG disclosure and information asymmetry, though findings are inconsistent. Ultimately, this review seeks to develop a conceptual framework that integrates the role of corporate governance in enhancing ESG disclosure as a mechanism to reduce information asymmetry, thereby contributing to existing literature and offering practical insights.